Tensile nanostructured hierarchically porous non-precious transition metal-based electrocatalyst for durable anion exchange membrane-based water electrolysis - Singh, Kailash; Selvaraj, Kaliaperumal (Journal of Colloid and Interface Science, 2024)
Electrochemical water electrolysis is a promising method for sustainable hydrogen production while transiting towards hydrogen economy. Among many, the Anion Exchange Membrane (AEM) based water electrolyzer is an emerging yet potentially affordable technology on maturity for producing large-scale hydrogen accommodating the usage of Non-Platinum Group Metal (non-PGM) based inexpensive electrocatalysts. Herein, we demonstrate the excellent performance of a bifunctional Nickel Copper Phosphide-Nickel sulphide (NCP-NS) electrocatalyst with a unique tensile nanostructure obtained via a facile, controlled ambient galvanic displacement route. An AEM electrolyzer with a larger active area of 10 cm(2) stacked with the symmetric NCP-NS electrodes and a membrane demonstrates scalability with a requirement of a mere 1.66 V to reach a current density of 10 mA cm(-2). The nickel-copper phosphide boosts the kinetics of charge transfer between the electrode and electrolyte interface, while a unique combination of a few nickel sulphide phases present in the catalyst provides sufficiently appropriate active sites for the overall water electrolysis. For the first time, we report a room temperature performance of similar to 230 mA cm(-2) at 2 V for a non-PGM-based bifunctional electrocatalyst with exceptional durability for over 300 h of operation in an AEM water electrolyser with a retention rate of 95 %-97 % at a current density range of 80-800 mA cm(-2).
Keywords: AEM electrolyzer; Bifunctionality; Electrodeposition; Non-PGM based Electrocatalyst; stability

Highly active and durable MNS bifunctional electrocatalysts for enhanced anion exchange membrane water electrolysis - Singh, Kailash; Yadav, Himanshu; Samdani, Kunda; Selvaraj, Kaliaperumal (Electrochimica Acta, 2025)
The development of non-platinum group metal (non-PGM) electrocatalysts with performance comparable to their noble metal counterparts remains a significant challenge for overall water splitting. In this study, we demonstrate the performance of an Anion Exchange Membrane (AEM) water electrolyzer using a bifunctional, non-PGM electrocatalyst: reduced graphene oxide (rGO)-encapsulated MoS2/Ni3S2 (MNS) grown on a nickel foam (NF) substrate. The rGO/MoS2/Ni3S2 (rGO-MNS) electrode was synthesized via a facile, single-step hydrothermal method. For the hydrogen evolution reaction (HER), the rGO-MNS electrode exhibited a low overpotential of 94 mV at a current density of 100 mA cm-2, maintaining excellent stability over 50 h with a minimal degradation rate of 120 mu V h-1. In the case of the oxygen evolution reaction (OER), an overpotential of 410 mV was required to reach the same current density, with a similarly robust durability and a degradation rate of only 360 mu V h-1. When employed as symmetric electrodes for overall water electrolysis, the rGO-MNS system achieved a current density of 10 mA cm-2 at a cell voltage of 1.51 V, outperforming the benchmark Pt/C & Vert;Ru/C catalyst pair, which required 1.58 V to reach the same performance. The enhanced electrocatalytic activity and durability are attributed to the conductive rGO encapsulation, which facilitates charge transfer and mitigates surface oxidation of the catalyst. These results present a promising strategy for designing cost-effective, durable, and highperformance non-PGM electrodes for AEM water electrolysis.
Keywords: Anion Exchange Membrane Water Electrolysis; Bifunctional Electrocatalyst; hydrogen evolution reaction; Oxygen Evolution Reaction; rGO-MNS

Material selection for enhanced performance in anion exchange membrane water electrolyzers: a study of membranes and gaskets - Singh, Kailash; Selvaraj, Kaliaperumal (Industrial & Engineering Chemistry Research, 2025)
Anion exchange membrane water electrolyzer (AEMWE) is an emerging technology for large-scale hydrogen production, where membrane electrode assembly (MEA) plays a critical role in the electrolyzer efficiency. This study investigates the effects of different membranes (Piperion, Aemion, and Sustainion) and gaskets (Viton, poly(tetrafluoroethylene) (PTFE), and Silicon) using a non-platinum group metal (non-PGM) bifunctional electrocatalyst under fixed compression and flow rates. Membrane properties such as ionic resistance and diffusion and gasket properties like thermal suitability and compressibility significantly affect the overall performance of AEMWE. The results indicate that Sustainion and Aemion membranes are best suited for lab-scale and industrial applications, respectively, while Silicon and PTFE gaskets are optimal for corresponding scales. Understanding these effects can help to improve the efficiency and guide material selection. This study provides valuable insights for researchers developing AEMWE technology, enabling advancements from laboratory research to megawatt-level industrial hydrogen production and supporting the transition to clean-energy solutions.

Integrated cell engineering and scale-up of a non-PGM bifunctional electrocatalyst for durable AEM water electrolysis - Singh, Kailash; Kavitha, T.; Selvaraj, Kaliaperumal (Sustainable Energy & Fuels, 2026)
Developing a scalable and sustainable non-Platinum Group Metal (non-PGM) bifunctional electrocatalyst for Anion Exchange Membrane (AEM) water electrolyzers remains a significant challenge, particularly at industrially relevant scales. Most reported non-PGM catalysts are demonstrated on small electrode areas (typically <= 2 cm(2)), making scalability a major bottleneck. Issues such as achieving uniform catalyst coating, maintaining similar structural morphology, and preventing activity loss due to leaching become increasingly prominent at larger scales. Therefore, a Nickel Copper Phosphide-Nickel Sulphide (NCP-NS) catalyst was developed and successfully scaled-up to >10 cm(2) electrode active area, and its performance was evaluated in an electrolyzer cell. A larger 13 cm(2) AEM cell was developed by addressing key parameters: (i) electrode design (mass loading density), (ii) assembly conditions (torque and gasket thickness), (iii) operational parameters (flow rate and temperature), and (iv) engineering aspect measurements (Fujifilm pressure distribution and interfacial contact resistance). These optimizations resulted in a high current density of 1012 mA cm(-2) at 2 V, with the stack maintaining 98% of its performance after 100 hours of continuous operation. The electrocatalysts delivered 55.96 kWh kg(-1) energy efficiency at 2 V. This work demonstrates how systematic scale-up and cell engineering can bridge the gap between lab-scale innovation and commercial application.